Immunoglobulin G galactosylation levels are decreased in systemic sclerosis patients and differ according to disease subclassification. (3rd March 2020) - Liu, Q; Lin, J; Han, J; Zhang, Y; Lu, J; Tu, W; Zhao, Y; Guo, G; Chu, H; Pu, W; Liu, J; Ma, Y; et al.
Abstract : Objectives : Scleroderma is a connective tissue immune disease that features collagen overproduction and can be categorized into two subtypes, localized scleroderma (LSc) and systemic sclerosis (SSc). SSc is clinically classified into two subsets: limited cutaneous (lcSSc) and diffuse cutaneous (dcSSc) SSc. The immunoglobulin G–galactosylation (IgG-Gal) ratio is abnormal in a number of immune diseases and has not been evaluated in SSc. Method : The study recruited 93 LSc patients, 298 SSc patients, and 436 healthy controls. N-glycans of purified IgG were obtained from plasma and detected by tandem mass spectrometry. The IgG-Gal ratio was measured by calculating the relative intensities of agalactosylated (G0), monogalactosyl (G1), and digalactosyl (G2) N-glycans according to the formula G0/(G1 + G2 × 2). Furthermore, we examined whether the IgG-Gal ratio differed between different subtypes of SSc. Results : The IgG-Gal ratio was significantly higher in SSc patients (1.139 ± 0.870) than in LSc patients (0.485 ± 0.280) and controls (0.395 ± 0.190). The IgG-Gal ratio successfully distinguished SSc patients from LSc and controls (area under the curve = 0.88 and 0.81, respectively). The IgG-Gal ratio was significantly higher in dcSSc patients than in lcSSc patients and increased along with increases in modified Rodnan skin score (p = 6.03 × 10 −5, Pearson's coefficient = 0.26) and erythrocyte sedimentation rate (p = 2.95 × 10 −10, Pearson's coefficient = 0.38). Conclusion : IgG-Gal ratios were abnormal in SSc patients and were associated with disease severity. The IgG-Gal ratio therefore shows potential as a biomarker for the diagnosis of SSc.